Investigating a surface water quality monitoring approach for QwaQwa, South Africa, by combining biological in vitro tests and chemical analyses - Avenant, Marinda; Börnick, Hilmar; Graumnitz, Stephanie; Nyoka, Ngitheni; Opeolu, Beatrice; Voua Otomo, Patricks; Schubert, Annika; Schubert, Sara; Vos, Tascha; Jungmann, Dirk (Frontiers in Water, 2024)
IntroductionWater quality assessment is a fundamental requirement for comprehensive water management. Access to water is not exclusively a quantitative issue, as human activities often lead to negative impacts on water quality due to pollution. This results in a need for the systematic monitoring of water bodies to surveil ongoing pollution dynamics and, if needed, facilitate the implementation of suitable solutions for water quality management.MethodsTo that effect, in March 2022 and July 2023, we conducted two sampling campaigns in four headwater streams in QwaQwa, South Africa, to assess the water quality under high (summer) and low (winter) flow conditions. The overarching aim was to support local decision-makers with relevant information on water quality in a semirural and less studied area. Beside the hydrological characterization of the catchment, which drains the mountainous areas around Phuthaditjhaba (the main town of the region), physicochemical and biological monitoring were conducted, including in vitro tests detecting endocrine disruption, dioxin-like impacts, and genotoxic potentials in the water.ResultsThe elemental analysis showed that at several sampling sites, Al, Cu, Mn, Fe, and Zn were above the Target-Water-Quality-Range (TWQR) for aquatic ecosystems and Fe, Al, and Mn were additionally above the TWQR for domestic use. Interestingly, the organic micropollutants (OMPs) revealed a region with a high incidence of HIV infections, given the occurrence of the drugs efavirenz, its transformation product 8-OH-efavirenz and nevirapine, among other micropollutants. Possibly, the signals from the in vitro tests for endocrine disruption are also induced by the detected micropollutants. Our results ultimately show that even though anthropogenic impacts increase from upstream to downstream, none of the sampling sites are without concern. This indicates the urgent need for measures to increase the water quality of these headwater streams in this region.